Health crisis: Human Papillomavirus Vaccine - Vergel Rodríguez, M.M. (Revista Española de Comunicación en Salud, 2016)
Currently the sanitary information would be able to catalogue of well public and more still in situations of sanitary crisis. For which the sanitary authorities should be felt in the obligation to offer an information contrasted, complete and prudent, for which the sanitary institutions possess numerous sources to the ones that to respond, elaborate in recent years, For the effective communication and well carried out of risks and/or sanitary crisis. Another agent that is determinant in the communication in these cases is the mass media, which should watch for a not alarmist and trustworthy information. So that when a crisis happens or sanitary risk, they interact sanitary institutions, population and mass media, being fundamental an adequate flow of information. But, that adequate flow exists? The information processing on the part of both is adapted? In this article, after valuing their actions with international guides and codes of good practices through a current event in Spain is deduced that is correct with some shades and that interests exist more than influence in this crisis and that, possibly, themselves they are not known of collective form.